Legal Protection of UMKM in Digital Marketing Based on Law No 20 Of 2008 and Law No 8 of 1999 - Jordy William Hutagalung; Martono Anggusti; Ria Juliana Siregar (Journal of Legal and Cultural Analytics, 2025)
The development of information and communication technology (ICT) has had a major impact in various fields, including in the business sector. One of the main influences is the shift towards a digital world that affects various sectors, including Micro, Small, and Medium Enterprises (MSMEs), in managing their markets through digitization. This digitalization process has made it easier for MSMEs to grow, develop, and market their products to international consumers.  MSMEs play a very important role in the Indonesian economy, contributing greatly to gross domestic product (GDP), job creation, and income generation. Various digital platforms, such as social media, e-commerce, and websites, allow MSMEs to reach consumers around the world. However, this digital transformation also brings challenges for MSMEs, such as legal issues, data privacy, and potential misuse of information. Indonesian regulations, such as Law No. 20/2008 on Micro, Small, and Medium Enterprises (UMKM Law) and Law No. 8/1999 on Consumer Protection (Consumer Protection Law), emphasize the importance of the legal system for MSMEs in the face of digital developments. These laws provide guidelines for MSMEs to operate effectively in the ever-changing digital ecosystem.